Respuesta :

Answer:

(9/2, 4/3) or just x = 9/2, y = 4/3. (it's the same thing)

Step-by-step explanation:

First, multiply the first equation 2x + 3y = 13 by 2, so that you get 4x + 6y = 26. Now you have the same coefficient for y. Now, subtract the second equation 6y = 8 (i simplified it first) from the first one that is doubled. After that, you would have just one equation, 4x = 18. So x = 18/4 = 9/2. Substitute x to solve for y, and you'd get 4/3.

9514 1404 393

Answer:

  (x, y) = (-6, 8 1/3)

Step-by-step explanation:

The system of equations appears to be ...

  • 2x +3y = 13
  • 6x +6y = 14

Dividing the first equation by 2 gives ...

  3x +3y = 7

Subtracting the first equation from this, we get ...

  (3x +3y) -(2x +3y) = (7) -(13)

  x = -6

Then substituting for x in the first equation, we have ...

  2(-6) +3y = 13

  3y = 25 . . . . . . . . add 12

  y = 25/3 = 8 1/3 . . . . divide by 3

The solution is (x, y) = (-6, 8 1/3).

Ver imagen sqdancefan
ACCESS MORE